Towards comprehensive project tooling in distributed projects : Autoethnographic account of FORESAIL nanosatellite project - Tammi, Jani (My University, 2018)
This thesis studies how tooling outcomes can be improved for distributed projects. Tools are important for almost any type of project work but for distributed projects they are of paramount importance. The very nature of distributed work makes it reliant on tools for managing tasks, providing the means of communication, maintaining and distributing knowledge, enabling access to shared data and managing the organization itself. These tools are commonly selected for projects based on the type of work being done, the availability of pre-existing infrastructure in the organization, the policies in effect, the lessons learned from earlier projects and the judgement of the project management. This activity, also known as “tooling”, commonly has a very limited scope and may be limited only to fulfill the needs of project management or only the needs of knowledge management, for example. This approach may result in overlapping functions, the creation of redundant data, increased running costs or worker dissatisfaction. The contribution of this thesis is twofold. Firstly, it increases the knowledge in the field distributed projects through an autoethnographic account of a distributed academic project during the first half of 2018. Secondly and more prominently, a new concept of Project Tooling is formulated, and a ground work is laid for future research on this concept. Project Tooling is built on other fields of research that commonly already have this concept in some form, even if not fully developed in all cases. This research draws on the existing body of literature to synthesize Project Tooling and then reflects it on the experiences and findings of the distributed research project account. The developed concept is a specific management activity which does not replace the existing tooling but supports them by proposing added steps ranging from the review of combined tooling decisions to the auditing of tool usage and adaptive measures to tools and usage patterns during the project execution. Project Tooling concept offers strategies to address the issues that may result from the traditional fragmented tooling approach.
Keywords: project management, tooling, project, distributed collaboration